Faktor-Faktor yang Mempengaruhi Self Directed Learning Readiness pada Mahasiswa Tahun Pertama, Kedua, dan Ketiga di Fakultas Kedokteran Universitas Hasanuddin dalam PBL - Hasan Nyambe; Harsono Mardiwiyoto; Gandes Retno Rahayu (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: The study explores the factors that affecting the readiness to (self-directed learning readiness) in the context of PBL is still rare, especially when in fact unprepared students in the initiative and the desire for self-learning, a lack of understanding of students on independent learning and interpretation mischaracterized the self-learning (self directed learning) is still frequently encountered. This study aimed to measure simultaneously identify factors that influence student SDLR in the first, second and third at the Medical Faculty of Hasanuddin University.Method: through two stages (sequencing), which combines two research approaches, namely qualitative as the main approach (dominant) and quantitative approaches as facilitators (less dominant). data collection with questionnaires and focus group discussions. The number of subjects quantitative 399 people (143 people from the first year, 152 the second year and 104 people from the third year), while for FGD about 18 people who set out with purposive sampling. Distributing questionnaires carried out in advance to obtain SDLR categories of high, medium and low, followed by FGD each batch by category SDLRnya. The analysis starts with the transcription process then the coding process.Results: This study shows that the average score lowest SDLR owned by First-year students FK UNHAS while the highest SDLR owned by Second year students. Not found SDLR category lower because students have had plenty of experience of active and independent learning that develops steadily. There are several factors that affect SDLR construct the desire to learn, self-control and self-management.Conclusion: Factors that affect SDLR the first year students, second and third in the FK Unhas divided into two, namely: (1) internal factors which consist of physical health, the availability of leisure time, hobby or avocation, self maturity, and intelligence; (2) external factors which consists of the support of family and friends, faculty facilities, problems, relationships between peers, and the influence of parents and friends